The Influence of Human Resource Development and Competence on Employee Performance at the Office of Women’s Empowerment and Child Protection of North Maluku Province - Alfariezzy Turuy, Muhammad Gybrant; Zulkifli, Zulkifli; Buamonabot, Irfandi (International Journal of Business, Law, and Education, 2026)
This study examines the partial and simultaneous effects of human resource development and competence on employee performance at the Office of Women’s Empowerment and Child Protection (DP3A) of North Maluku Province. This research uses a quantitative approach, with data collected through questionnaires distributed to 60 respondents. The data were analyzed using SPSS 26, with data quality testing, classical assumption testing, and multiple linear regression. The results indicate that human resource development and competence have a significant, simultaneous effect on employee performance. These findings suggest that strengthening employee capabilities through continuous development programs and competency enhancement can improve work performance within the agency. Overall, this study concludes that human resource development and competence are strategic factors in improving employee performance and supporting the achievement of organizational goals at the DP3A Office of North Maluku Province.